Autoimmune thyroid disease and ovarian hypofunction: a review of literature - Ru Wang; Youyuan Lv; Tao Dou; Qian Yang; Chunxiao Yu; Qingbo Guan (BMC, 2024)
Abstract Thyroid hormones(THs) are essential for the proper functioning of the ovaries, and multiple studies have shown that thyroid abnormalities, especially during adolescence and reproductive age, can lead to lifelong ovarian dysfunction. Autoimmune thyroid disease (AITD), one of the most common organ specific autoimmune diseases, is mainly mediated by cellular autoimmune reactions, and has strong inflammatory infiltration and immune active cells, including chemokines and cytokines, which are important components of ovarian aging. This suggests that autoimmune and inflammatory molecular processes may play a role in the emergence of ovarian dysfunction. The purpose of this review is to summarize recent in vivo and in vitro evidence of a complex relationship between AITD and ovarian dysfunction. AITD is closely related to the decline of ovarian function from the perspective of antibody, cytokine, oxidative stress, and genetic factors. Finally, some of the currently known treatments for AITD and hypo ovarian disease are summarized.